소아에서 복부 고형 장기 손상의 치료에 대한 분석 - 장지나(Jina Chang); 최금자(Kum-ja Choi) (Annals of surgical treatment and research, 2009)
Purpose: In pediatric solid organ injury, non-operative management is considered as a standard treatment when the patient is hemodynamically stable. However, treatment according to the injured organ and the depth of injury is controversial. The purpose of this study is to evaluate treatment results in the management of abdominal solid organ injuries in children. Methods: This analysis was performed retrospectively with 57 consecutive children under 15 year of age who were diagnosed with abdominal solid organ injuries at Ewha Womans University Mokdong Hospital from January, 1999 to June, 2007. Results: The major cause of pediatric solid organ injury was traffic accidents (59.6%) and the most frequently injured organ was the liver (66.7%). 54 patients (94.7%) were treated non-operatively and the success rate was 100%. There was no difference in type of management and success rate according to the depth of injury or the injured organs. The average ICU stay was 4.3 days, and the average hospital stay was 13.6 days and that was extended depending on the depth of injury. And according to the cause of injury, cases by traffic accident stayed significantly longer than cases by other causes. Conclusion: High grade of injury is not contraindication of nonoperative management in pediatric solid organ injury. Hemodynamic instability is the only absolute indication of operation. Therefore, if the patient is stable, non-operative management with intensive observation is the choice of treatment. Purpose: In pediatric solid organ injury, non-operative management is considered as a standard treatment when the patient is hemodynamically stable. However, treatment according to the injured organ and the depth of injury is controversial. The purpose of this study is to evaluate treatment results in the management of abdominal solid organ injuries in children. Methods: This analysis was performed retrospectively with 57 consecutive children under 15 year of age who were diagnosed with abdominal solid organ injuries at Ewha Womans University Mokdong Hospital from January, 1999 to June, 2007. Results: The major cause of pediatric solid organ injury was traffic accidents (59.6%) and the most frequently injured organ was the liver (66.7%). 54 patients (94.7%) were treated non-operatively and the success rate was 100%. There was no difference in type of management and success rate according to the depth of injury or the injured organs. The average ICU stay was 4.3 days, and the average hospital stay was 13.6 days and that was extended depending on the depth of injury. And according to the cause of injury, cases by traffic accident stayed significantly longer than cases by other causes. Conclusion: High grade of injury is not contraindication of nonoperative management in pediatric solid organ injury. Hemodynamic instability is the only absolute indication of operation. Therefore, if the patient is stable, non-operative management with intensive observation is the choice of treatment. KCI Citation Count: 1